The Influence of E-Trust, Online Customer Review and E-Service Quality on the Purchase Decision of Products on the SOCO By Sociolla Application - Koto, Fitriza Ferunita; Wahyono, Seno Aji; Widyaningrum, Santi (MultiTech Publisher, 2024)
This research aims to investigate the influence of e-trust, online customer reviews, and e-service quality on product purchases on the SOCO By Sociolla application. SOCO By Sociolla is a leading beauty e-commerce platform in Indonesia that offers a wide range of beauty products online. The research utilizes a survey method by collecting data through questionnaires distributed via social media for 100 samples. The collected data is analyzed using regression analysis to examine the impact of independent variables (e-trust, online customer reviews, and e-service quality) on the dependent variable (purchase decisions). The research sample consists of Indonesian users of the SOCO By Sociolla application. The analysis results indicate that e-trust does not significantly affect purchase decisions, but online customer reviews and e-service quality have a significant impact. Overall, e-trust, online customer reviews, and e-service quality collectively influence purchase decisions on the SOCO By Sociolla application.